O15.5 The natural history of chlamydia trachomatis infection in women: a multi-parameter evidence synthesis. (13th September 2015) - Price, MJ; Ades, AE; Soldan, K; Welton, NJ; Macleod, J; Simms, I; De Angelis, D; Turner, KME; Horner, PJ
Abstract : Introduction: The National Chlamydia Screening Programme (NCSP) was initiated in England in 2003. However, the evidence base supporting it has been questioned repeatedly, with little consensus on modelling assumptions, parameter values, or evidence sources to be used in cost-effectiveness analyses. Methods: We reviewed all the available evidence on the Chlamydia trachomatis (CT) in the UK and its sequelae. Evidence was identified using "high yield" strategies. Bayesian Multi-Parameter Evidence Synthesis models were constructed for separate sub-parts of the clinical and population epidemiology of CT. Where possible different types of data were statistically combined to derive coherent estimates. Where evidence was inconsistent, evidence sources were re-interpreted and new estimates derived on a post hoc basis. Results: An internally coherent set of estimates was generated, consistent with a multi-faceted evidence base. Among the key findings were: the risk of pelvic inflammatory disease (PID), both symptomatic and asymptomatic, following an untreated CT infection is 17% (6, 29), and the risk of salpingitis is 7% (2, 14). In women aged 16–24 screened at annual intervals, at best 61% (55, 67) of CT-related PID and 22% (7, 43) of all PID could be prevented. For women aged 16–44 in the UK, the proportions of PID, ectopic pregnancy and tubal factor infertility (TFI) that are attributable to CT are estimated to be 20% (6, 38), 5% (1, 12), and 29% (9, 56) respectively. Conclusion: The study establishes a set of interpretations of the major studies and study designs, under which a coherent set of estimates can be generated for UK decision-makers. CT is a significant cause of PID and TFI. CT screening is of benefit to the individual, but detection and treatment of incident infection may be more beneficial. Further research is required to confirm predictions, and to improve the precision of key estimates. The cost-effectiveness of screening should be re-evaluated using these estimates. Disclosure of interest statement: This study was funded by the Medical Research Council grant G0801947. No pharmaceutical grants were received in the development of this study. PH has received funding from Cepheid directly and indirectly for lecturing on point of care testing and undertaking research on the cost effectiveness of their CT/NG assay. Has also received payment from Atlas Genetics for an article in the Parliamentary Review on the benefits of point of care technology in improving the cost effectiveness of sexual health services. Has also received an honorarium from Hologic for an education talk on STI diagnostics.